Using the template for intervention description and replication (TIDieR) as a tool for improving the design and reporting of manual therapy interventions. (August 2016) - Alvarez, Gerard; Cerritelli, Francesco; Urrutia, Gerard
Abstract: The detailed reporting of any research intervention is crucial to evaluate its applicability into a routinely practice-based context. However, it has been estimated that, especially in non-pharmacological interventions, the published literature typically includes incomplete intervention details. In the field of manual medicine, where interventions are delivered with a high degree of individualization and variability, poorly reported studies could compromise internal and external validity of the results. Among the various initiatives that have been undertaken to improve the intervention description, theT emplate forI nterventionD escription andR eplication (TID ieR ) has to be highlighted as the most promising.TID ieR offers both to researchers and clinicians a helpful and comprehensive guidance on how manual therapy interventions have to be designed and reported, taking into account the clinical complexity of manual therapy and the need to satisfy research gold standards. Highlights: Good reporting of research interventions is crucial to assess study validity. In manual therapies lack of reporting significantly affects results generalizability. TIDieR is a comprehensive guideline on how manual interventions shall be reported.